Repurchase intention in modern retail: A moderation analysis of experience marketing in affecting consumer behavior - Andreas Ari Sukoco; Cheryl Marlitta Stefia; Rakotoarisoa Maminiaina Heritiana Sedera; Ansar Abbas (Universitas Ahmad Dahlan, 2025)
In the increasingly competitive modern retail sector, understanding the determinants of consumer repurchase intention has become essential for sustaining customer loyalty and long-term profitability. This study aims to examine the effects of product quality, price perception, and promotion on repurchase intention, while further analyzing the moderating role of experience marketing. Employing a cross-sectional survey design, data were collected from 120 purposely selected consumers who had recently purchased products at Super Indo outlets in Yogyakarta, Indonesia. A structured questionnaire using a five-point Likert scale was administered, and the instrument was verified through validity and reliability testing. Data analysis included descriptive statistics, hypothesis testing, and moderated regression analysis to evaluate both direct and interaction effects. The findings reveal that product quality, price perception, and promotion significantly influence repurchase intention. Moreover, experience marketing enhances the impact of product quality and price perception on repurchase intention, but does not moderate the relationship between promotion and repurchase intention. These results underscore the importance of integrating consumer experience into product and pricing strategies, while reevaluating promotional activities beyond short-term incentives. The study provides empirical contributions to consumer behavior research in developing economies and offers practical insights for retail managers seeking to foster sustainable customer loyalty.